2020
DOI: 10.3390/ani10101898
|View full text |Cite
|
Sign up to set email alerts
|

Welfare Benefits of Intradermal Vaccination of Piglets

Abstract: Vaccination is reported as a stressful and painful event for animals. This study investigated whether needle-free intradermal vaccination improves the welfare of weaned pigs through the reduction of stress and pain biomarkers and improvement of behavioural parameters compared to traditional intramuscular injection with a needle. A total of 339 weaned piglets were allocated to 3 treatment groups: Intradermal Application of Liquids (IDAL) pigs, vaccinated against Porcine Circovirus type 2 (PCV2) by means of intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 30 publications
1
24
2
Order By: Relevance
“…This agrees with the results presented by Scollo et al ( 14 ) and Temple et al ( 13 ) with regard to differences between intradermal and intramuscular administration, although Scollo et al ( 14 ) did not use a Control group and Temple et al ( 13 ) found no differences between the control and intradermal groups. Actually, the percentage of piglets that vocalized during the vaccination was slightly lower in Temple et al ( 13 ), 7, 7, and 32% for the Control, intradermal, and intramuscular groups, respectively, as compared to Scollo et al ( 14 ), who reported 45 and 75% for intradermal and intramuscular administrations, respectively, and to the present study, with 12, 52, and 88% for the Control, Hipradermic, and IM treatments, respectively. However, a reason for this difference could be that Temple et al ( 13 ) considered just high-pitched vocalizations assessed by direct observation, and not recorded.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This agrees with the results presented by Scollo et al ( 14 ) and Temple et al ( 13 ) with regard to differences between intradermal and intramuscular administration, although Scollo et al ( 14 ) did not use a Control group and Temple et al ( 13 ) found no differences between the control and intradermal groups. Actually, the percentage of piglets that vocalized during the vaccination was slightly lower in Temple et al ( 13 ), 7, 7, and 32% for the Control, intradermal, and intramuscular groups, respectively, as compared to Scollo et al ( 14 ), who reported 45 and 75% for intradermal and intramuscular administrations, respectively, and to the present study, with 12, 52, and 88% for the Control, Hipradermic, and IM treatments, respectively. However, a reason for this difference could be that Temple et al ( 13 ) considered just high-pitched vocalizations assessed by direct observation, and not recorded.…”
Section: Discussionsupporting
confidence: 91%
“…For instance, a papule in the Hipradermic and a blood spot in the intramuscular groups were seen up to 10 min after vaccination, but the presence of crusts and redness areas achieved a maximum in both treatments just at the end of the assessment of activity budgets the day of vaccination (8 h after vaccination) and were maintained in similar values the day after (30 and 58% of crust in Hipradermic and IM treatments, respectively, and 33–24% and 25–21% of redness areas the day of the vaccination–day after the vaccination in the Hipradermic and IM treatments, respectively). These results disagreed with those obtained by Temple et al ( 13 ), where the piglets vaccinated intramuscularly did not show any visible reaction, but in accordance with these authors, the piglets from the present study did not present any abscess-like reaction 21 days post-vaccination.…”
Section: Discussioncontrasting
confidence: 67%
See 3 more Smart Citations